Utilization of Trash Fish for Cultivation of Crablet Mud Crab (Scylla serrata) - Heppi Iromo; Dori Rachmawani; Abdul Jabarsyah; Zainuddin Zainuddin (Marine Science Department Diponegoro University, 2020)
The high demand for mud crabs in North Kalimantan causes catch to increase in the wild. If it is not balanced with efforts to increase its aquaculture of mud crab, in the future there will be a decline in population. This study aims to determine the growth and survival rate of mud crab seed (crablet, Scylla serrata) in the application method of different types of trash fish. This research used a completely randomized design with 4 treatments and 3 replications. The Crablet used carapace width average 0.07-0.09 cm and weigh average 0.05-0.07 g with total 150 crablets. The treatments applied by trash fish were (A) Tilapia Fish (Oreochromis mossambicus), (B) Longfin Herrings Fish (Ilisha elongata), (C) Sword Fish (Trichiurus lepturus) and (D) Snails (Telescopium telescopium). The results were The best weight growth of crablet occurs in the treatment of T. lepturus (P>0.05) and the highest of survival rates of crablet were found in treatment T. telescopium (P<0.05) than the other. The trash fish were used turned out to be able survival of crablet mud crab (Scylla serrata).